High-resistant starch and low-glutelin content 1 rice benefits gut function in obese patients - Zhou, Tiantian; Tang, Zhaocheng; Liu, Ru; Gui, Linxing; Luo, Wenzhen; Yang, Yuwen; Zhang, Baolong (Frontiers in Sustainable Food Systems, 2024)
The intestinal microbiota plays a crucial role in human health, yet the impact of highresistant starch and low-glutelin rice in the gut of obese individuals remains unexplored. In this study, different types of rice, namely japonica rice (control), low-glutelin content 1 rice (Lgc1), high-resistant starch and low-glutelin content 1 rice (HR+Lgc1), and commercially available low-glycemic index rice (LowGI), were utilized as samples to examine their in vitro digestion and fermentation, as well as the impact of HR+Lgc1 on the intestinal microbiota in obese individuals. The findings revealed that HR+Lgc1 rice exhibited lower in vitro digestion rates for starch and protein compared to the other three types. Following 24 h of in vitro fermentation, the total short-chain fatty acid content in HR+Lgc1 was 108.67 mmol/L, which was 60.33%, 51.26%, and 17.29% that in control, Lgc1, and LowGI, respectively. Moreover, HR+Lgc1 rice displayed an inhibitory effect on the production of harmful branched-chain fatty acid metabolites. Analysis through 16S rDNA sequencing indicated that, after fermentation, HR+Lgc1 significantly enhanced the abundance of beneficial bacteria such as Bifidobacterium, Parabacteroides, and Faecalibacterium in the gut, whereas it reduced the abundance of harmful bacteria such as Escherichia_shigella. Our findings may contribute to the development of new foods rich in dietary fiber to improve the digestive function of patients with multiple comorbidities.